2014
DOI: 10.3171/2014.4.peds13464
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cerebral aneurysms in children: analysis of the Kids' Inpatient Database

Abstract: Object Endovascular coiling and surgical clipping are viable treatment options of cerebral aneurysms. Outcome data of these treatments in children are limited. The objective of this study was to determine hospital mortality and complication rates associated with surgical clipping and coil embolization of cerebral aneurysms in children, and to evaluate the trend of hospitals' use of these treatments. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 30 publications
1
21
1
3
Order By: Relevance
“…This increase may be due to the International Subarachnoid Aneurysm Trial (ISAT) results [21] trending toward endovascular management, associated with the parental tendency to refuse open brain surgery [4]. Although observational studies have also suggested that children treated by endovascular therapy had a better outcome than those treated by surgical clipping, most of them are uncontrolled and small [22]. Agid et al [3] found good results in 77% of their endovascular group against only 44% in the surgically treated group, independently of Hunt and Hess grading.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This increase may be due to the International Subarachnoid Aneurysm Trial (ISAT) results [21] trending toward endovascular management, associated with the parental tendency to refuse open brain surgery [4]. Although observational studies have also suggested that children treated by endovascular therapy had a better outcome than those treated by surgical clipping, most of them are uncontrolled and small [22]. Agid et al [3] found good results in 77% of their endovascular group against only 44% in the surgically treated group, independently of Hunt and Hess grading.…”
Section: Discussionmentioning
confidence: 99%
“…Lasjaunias et al [2] also reported a better outcome with endovascular treatment, with 7 of 8 treated patients having a good outcome. In a database analysis of 1,120 children, Alawi et al [22] found an overall in-hospital mortality that was threefold lower in the coil embolization group in comparison to the surgical clipping group, with higher risks of hydrocephalus, systemic infections and pulmonary complications in the latter. Likewise, infants had the highest mortality rate compared to other children, possibly related to greater tendency to hemorrhage and higher prevalence of posterior circulation giant aneurysms [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies seeking to investigate relatively rare pediatric diseases or conditions would be relevant applications of big data as these inquiries would be supported by much larger sample sizes than are obtainable by individual centers. Notable examples of such studies include wartime head injury, myelomeningocele, cerebral aneurysms, and venous thromboembolism in children with traumatic brain injury [40-44]. Big data can provide information on the associations of hospital type, provider caseload, and geography with outcomes, as has been nicely done for pediatric brain tumors, shunt surgery, and cerebrovascular pathology [37, 38, 45].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, aneurysms in the cavernous segment of the ICA, which are often difficult to treat with microsurgery, can readily be approached by endovascular methods [19]. Endovascular treatment of aneurysms is associated with lower mortality compared to microsurgical clipping in the pediatric population [20]. …”
Section: Discussionmentioning
confidence: 99%